PREVALENSI ADOLESCENT IDIOPATHIC SCOLIOSIS : LITERATURE REVIEW - Ramadhani, Alinda Nur; Romadhoni, Dea Linia (Universitas Tribhuwana Tunggadewi, 2022)
Adolescent idiopathic scoliosis is a musculoskeletal disorder characterized by three-dimensional changes in the vertebrae that occur in children aged 10-18 years. The purpose of this study was to determine the prevalence of adolescent idiopathic scoliosis through a literature review. Research article searches were carried out in the PubMed and BMC Central databases using the keywords “adolescent”, “idiopathic”, “prevalence” and “prevalence” from 2010 to 2020. Articles in English and Indonesian were selected using keywords, and 389 articles were found. The articles were then selected based on the exclusion and inclusion criteria, leaving 5 articles to be reviewed. The prevalence of adolescent idiopathic scoliosis is higher in girls than boys and the prevalence increases with age. The prevalence of adolescent idiopathic scoliosis varies between 0.72-4.3%.